1997
DOI: 10.1017/s0031182097001480
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Ascaris suum infection in the pig: worm population kinetics following single inoculations with three doses of infective eggs

Abstract: To study population kinetics during primary Ascaris suum infections, 3 groups of 52 pigs each were inoculated with 100, 1000, or 10,000 infective eggs. In all groups, the majority of larvae was found in the liver on day 3 post inoculation (p.i.) and in the lungs on day 7 p.i. Liver white spots, caused by migrating larvae, were most numerous at day 7 p.i., whereafter they gradually healed, and only low numbers of granulation-tissue type white spots and lymphonodular white spots persisted at days 21-56 p.i. Inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
110
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(123 citation statements)
references
References 12 publications
13
110
0
Order By: Relevance
“…Most larvae are expelled from pig (and probably also human) hosts at an early stage, when they are too small to be observed by the naked eye (Roepstorff et al, 1997;Nejsum et al, 2009). Macroscopic Ascaris worms in faeces are seen only in a minority of cases.…”
Section: Diagnosismentioning
confidence: 99%
“…Most larvae are expelled from pig (and probably also human) hosts at an early stage, when they are too small to be observed by the naked eye (Roepstorff et al, 1997;Nejsum et al, 2009). Macroscopic Ascaris worms in faeces are seen only in a minority of cases.…”
Section: Diagnosismentioning
confidence: 99%
“…Recent comparative studies on larval migration in pigs and mice have led to the suggestion that the mouse is a suitable model for exploring susceptibility in the early phase of A. suum infection Slotved et al 1998) as the pattern of migration of the larvae is analogous. The recovery of larvae from mice has been shown to be higher when compared to other abnormal hosts such as rabbits, guinea-pigs and rats (Douvres and Tromba, 1971) and even pigs (Roepstorff et al 1997). Relative host size and parasite size contribute to this higher recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, on return to the small intestine post migration, pre-adult larvae shift distally and are expelled between days 14-21 p.i. This pattern of self-cure expulsion was observed during experimental single infections and did not appear to be influenced by the size of the inoculation dose [28].…”
Section: The Immunological Response To Ascaris Infectionmentioning
confidence: 54%
“…in pigs coincides with the healing of GT-WS [28]. Peréz et al [40] Increased liver pathology has been shown to be related to a reduction in lung larval numbers in repeated experimental inoculations [26,29,42] and in consistently naturally-exposed herds [26].…”
mentioning
confidence: 99%